“Writing Javanese Script” Application as a Support for Learning to Write Javanese Script in Junior High Schools - Kholifaturrohmah, Nur; Insani, Nur Hanifah (Journal of Education Reseach and Evaluation, 2025)
The ability of Grade VIII students at SMP to write in Javanese script remains relatively low, indicating the need for more effective learning media to improve student learning outcomes. This study aims to determine the effectiveness of the "Nulis Aksara Jawa" application as a learning medium in teaching Javanese script writing to Grade VIII students. The research employed a quasi-experimental method with a Nonequivalent Control Group Design, utilizing pre-tests and post-tests for data collection. The study involved Grade VIII students, with a total population of 256 and a sample of 64 students selected randomly. Data collection methods included observation, interviews, and tests, using questionnaires and test sheets as instruments. Quantitative data analysis was conducted using SPSS 30. The results showed that the control group had a pre-test score of 39.04 and a post-test score of 65.52, while the experimental group had a pre-test score of 51.52 and a post-test score of 86.12. The t-test results indicated a significant difference in Javanese script writing achievement between the experimental and control groups before and after using the learning media. The N-gain score for the experimental class was 70.47%. It is concluded that the "Nulis Aksara Jawa" application is an effective medium for learning to write in Javanese script. The implications of the research are that the learning media in the form of the “Nulis Aksara Jawa” application is suitable for use in learning.